93.1k views
4 votes
Y=(x-6)(x-2) in standard form

2 Answers

1 vote

Answer:

y = x² - 8x + 12

Explanation:

y = (x - 6)(x - 2)

y = x² - 2x - 6x + 12

y = x² - 8x + 12

User Abhinav Singh
by
4.5k points
0 votes

Answer:

x^2-8x+12=y

Explanation:

standard form of quadratic equation:

ax^2+bx+c=y

2)in order to rewrite this in standard form we need to use FOIL(first, outer,inner,last)

so:

x*x=x^2

x*-2=-2x

-6*x=-6x

-6*-2=12

x^2-2x-6x+12=y

x^2-8x+12=y

Hope this helps!

User Anusha Pachunuri
by
4.5k points